(3GdQSGdI GdbTjQjIs - (3YHO GdcQje Hf ghGRf Hf YHO Gdedc GHf WdMI GdfjSGHhQj GdbTjQj, CHh GdbGSe, Rjf GdESdGe,J (B465 (3g` s ((3Ydi Hf YHO GdbGOQ f CMeO Hf GdfLGQ s)
(3ChdgG (B:s
(3GdMeO ddg GdPi JaQO HLdGd edchJg gP g QSGdI cJHgG GdabjQ Edi Gddg JYGdi CHh GdbGSe YHO GdcQje Hf ghGRf GdbTjQi Zdi LeGYI GdUhajI HHdOGf GdESdGe CeG HYO abO LYd Gddg gPg GdWGFaI s
(3BNQgG (B:s
(3SeYJ JbQHkG Edi Gddg YR hLd hCgd GdUaG jNQLhf GdNdb hGdeYGQa Yf GdbdH JMbbkG HGddg YR hLd , agPg hUjJfG ddeQjOjf ,hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdYfhGfGJ HGdMeQI hGdNVQI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs